Impact of Notch3 Activation on Aortic Aneurysm Development in Marfan Syndrome. (15th February 2022) - Jespersen, Kathryn; Li, Chenxin; Batra, Rishi; Stephenson, Christopher A.; Harding, Paul; Sestak, Kylie; Foley, Ryan T.; Greene, Harrison; Meisinger, Trevor; Cook, Jason R.; Baxter, B. Timothy; Xiong, Wanfen
Abstract : Background . The leading cause of mortality in patients with Marfan syndrome (MFS) is thoracic aortic aneurysm and dissection. Notch signaling is essential for vessel morphogenesis and function. However, the role of Notch signaling in aortic pathology and aortic smooth muscle cell (SMC) differentiation in Marfan syndrome (MFS) is not completely understood. Methods . RNA-sequencing on ascending aortic tissue from a mouse model of MFS, Fbn1 mgR/mgR, and wild-type controls was performed. Notch 3 expression and activation in aortic tissue were confirmed with real-time RT-PCR, immunohistochemistry, and Western blot. Fbn1 mgR/mgR and wild-type mice were treated with a γ -secretase inhibitor, DAPT, to block Notch activation. Aortic aneurysms and rupture were evaluated with connective tissue staining, ultrasound, and life table analysis. Results . The murine RNA-sequencing data were validated with mouse and human MFS aortic tissue, demonstrating elevated Notch3 activation in MFS. Data further revealed that upregulation and activation of Notch3 were concomitant with increased expression of SMC contractile markers. Inhibiting Notch3 activation with DAPT attenuated aortic enlargement and improved survival of Fbn1 mgR/mgR mice. DAPT treatment reduced elastin fiber fragmentation in the aorta and reversed the differentiation of SMCs. Conclusions . Our data demonstrated that matrix abnormalities in the aorta of MFS are associated with increased Notch3 activation. Enhanced Notch3 activation in MFS contributed to aortic aneurysm formation in MFS. This might be mediated by inducing a contractile phenotypic change of SMC. Our results suggest that inhibiting Notch3 activation may provide a strategy to prevent and treat aortic aneurysms in MFS.